Karakteristik Penderita Tuberkulosis di Rumah Sakit Ibnu Sina Periode Januari - Desember 2018 (Characterization of Tuberculosis Patients in Ibnu Sina Hospital for January – December 2018) - Rachmat Faisal Syamsu; Nurqalbi Faizal; Sandra Kariati; Muhammad Zuhal Darwis; Andi Sri Nurul Hikmah Angraini (Halu Oleo University, 2020)
Background: Tuberculosis is a disease caused by Mycobacterium tuberculosis. These pathogenic bacteria attack the lungs and other body organs. The TB incidence rate in Indonesia determines the third highest in the world after India and China. Estimated every year an estimated 528,000 new TB cases with approximately 91,000 deaths. Purpose: The aims of this study was to determine the characteristics of tuberculosis sufferers in Ibnu Sina Hospital in the period January-December 2018. Methods: This research examines research using observational research by looking at secondary data from the medical records of Ibnu Sina Hospital . The population was 53 patients, taking a sample using the total sampling method. The study was conducted in January 2020 at Ibnu Sina Hospital. Data were analyzed electronically using Microsoft Excel 2016 computer software with a descriptive display and presented in tabular form. Patients with Tuberculosis were obtained (63,75%) and women (36,25%). Result: Terms of BMI obtained underweight sufferers (52,5%), normal (36,25%), overweight (7,5%), and obecitas 1 (3,75%). Of the age categories ≤ 5-14 years (5%), 15-24 years (16,25%), 25-44 years (21,25%), 45-64 years (36,25%), dan ≥ 65 years (21,25%). Based on the occupational groups obtained by employees (12,5%), self-employed (8,75%), laborers (21,25%), IRT (27,5%), students (10%), civil servants (1,25%), lecturer (1,25%), retired (1,25%), fisherman (1,25 %) and unemployed (13,75%). Conclusion: The criteria for tuberculosis sufferers from this study came fromgender. The scales of males were more than females, in terms of age at most at age 45-64 years, from IMT the most tuberculosis patients were thin, and from work suffered more by housewives and laborers.Keywords: tuberculosis, gender, body mass index, age, work ABSTRAKLatar Belakang: Tuberkulosis merupakan penyakit yang disebabkan oleh Mycobacterium tuberculosis. Bakteri patogen ini menyerang paru-paru dan organ tubuh lainnya.. Angka kejadian TB di Indonesia menempati urutan ketiga terbanyak di dunia setelah India dan Cina. Diperkirakan setiap tahun terdapat 528.000 kasus TB baru dengan kematian sekitar 91.000 orang. Tujuan: untuk mengetahui gambaran karakteristik penderita Tuberkulosis RS Ibnu Sina periode Januari-Desember 2018. Metode: Penelitian ini merupakan penelitian deskriptif dengan menggunakan pendekatan observasional dengan melihat data sekunder dari rekam medik RS Ibnu Sina. Jumlah populasi adalah 53 pasien, pengambilan sampel menggunakan metode total sampling. Penelitian dilakukan pada bulan Januari 2020 di RS.Ibnu Sina. Data dianalisa secara elektronik menggunakan perangkat lunak komputer program Microsoft Excel 2016 dengan tampilan deskriptif dan disajikan dalam bentuk tabel. Hasil: Didapatkan Penderita Tuberculosis laki-laki (63,75%) dan perempuan (36,25%). Dari segi IMT didapatkan penderita underweight (52,5%), normal (36,25%), overweight (7,5%), dan obesitas 1 (3,75%). Dari kategori umur ≤ 5-14 tahun (5%), 15-24 tahun (16,25%), 25-44 tahun (21,25%), 45-64 tahun (36,25%), dan ≥ 65 tahun (21,25%). Berdasarkan kelompok pekerjaan didapatkan karyawan (12,5%), wiraswasta (8,75%), buruh (21,25%), IRT (27,5%), pelajar / mahasiswa (10%), PNS (1,25%), dosen (1,25%), pensiunan (1,25%), nelayan (1,25%), dan yang tidak bekerja (13,75%). Simpulan: Kriteria penderita Tuberculosis dari penelitian ini didapatkan dari jenis kelamin menunjukkan laki-laki lebih banyak dari perempuan, dari segi umur paling banyak pada usia 45-64 tahun, dari IMT paling banyak penderita Tuberculosis yang underweight, dan dari pekerjaan lebih banyak diderita oleh ibu rumah tangga dan buruh.Kata Kunci: tuberculosis, jenis kelamin, indeks massa tubuh, umur, pekerjaan